Revolutionizing Content Creation: The Power of AI Language Models - Nitnaware, Piyush; Kawde, Prajwal; Dahiwale, Samyak; Bhuskade, Purva; Mandpe, Snehal; Patil, Leena (International Journal of Computer Sciences and Engineering, 2024)
The Open AI language model is a helpful tool in the generation of AI content. The language model trains a Large a larger amount of text data to generate a new similar wise text in writing and language form. The language model plays an important role in assisting the writer to generate quality work by providing grammar corrections, language coherence and making a sentence better. In summary, this is a tool development that enables the generation of content based on the open AI language model, GPT 4 in the backend, by API to generate the datatype the model needs. Via a tool, businesses can generate more quality content than before. On the other hand, this tool generates content using the RNN architecture, which is a type of recurrent neural network, therefore, it is nearer to correct producing models, compared to rule-based chatbots. Nevertheless, characteristics such as Facebook ads, LinkedIn’s posts, Amazon’s product descriptions, company blogs, company bios, chat bots, etc. will be available in the dashboard. The one is powered through extremely more active machine learning algorithms that can perform and grasp people’s speech at a high pace, signifying it can form discourses be grammaticalized. Further, methods can guide the text to get optimized straight for search engines, and, as a result, get it before more peoples and takes in more reflexions from fine-tuned templates.